2017
DOI: 10.1038/s41598-017-06826-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Monocyte Subsets in the Immunopathology of Giant Cell Arteritis

Abstract: Monocytes/macrophages are critical in systemic and local inflammation in giant cell arteritis (GCA) and possibly in clinically overlapping polymyalgia rheumatica (PMR). Therefore, we aimed to understand the contribution of monocyte subsets and the CX3CR1-CX3CL1 and CCR2-CCL2 migratory pathways, to the pathology of GCA. Peripheral blood monocytes were enumerated in samples from newly-diagnosed, untreated GCA and PMR patients and after prednisone-induced remission. The distribution of classical (CD14brightCD16ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 52 publications
5
50
1
Order By: Relevance
“…Although this was a retrospective study and most cases lacked data of peripheral blood lymphocyte subtype count, the lymphocyte count improved remarkably after treatment, which was in agreement with the previous studies. Sleen et al [23] indicated that peripheral blood monocyte count of GCA and PMR patients was higher than normal and decreased after treatment, which was similar to our findings. Some markers (such as matrix metalloproteinase-3, or small-vessel vasculitis and vasa vasorum vasculitis were observed in pathology) could be applied for predicting the presence of PMR or PMR-related symptoms in GCA patients [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Although this was a retrospective study and most cases lacked data of peripheral blood lymphocyte subtype count, the lymphocyte count improved remarkably after treatment, which was in agreement with the previous studies. Sleen et al [23] indicated that peripheral blood monocyte count of GCA and PMR patients was higher than normal and decreased after treatment, which was similar to our findings. Some markers (such as matrix metalloproteinase-3, or small-vessel vasculitis and vasa vasorum vasculitis were observed in pathology) could be applied for predicting the presence of PMR or PMR-related symptoms in GCA patients [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Th1 and CD8+ T cells are attracted by CXCL9 and CXCL10 , and Th17 cells are attracted by CCL20 . Monocytes enter the arterial wall under the influence of CCL2 and CX3CL1 , after which these cells differentiate into proinflammatory macrophages. B cells may migrate toward CCL20 and CXCL13 gradients in the arterial wall .…”
Section: Evidence For Distinct Gca Subsets Based On Immunologic Featuresmentioning
confidence: 99%
“…These monocytes differentiate into macrophages upon entering the tissue. 1,6 Some of the macrophages fuse and develop into multinucleated giant cells. 7 Macrophages in GCA lesions are derived from circulating monocytes, of which three subsets have been identified: classical CD14 high CD16 À cells, intermediate CD14 high CD16 + cells and nonclassical CD14 dim CD16 + cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although macrophages are one of the dominant inflammatory cellular infiltrates in GCA lesions, 6,[16][17][18][19] little is known about their phenotypic heterogeneity and spatial distribution within the affected vessel wall. We hypothesised that within GCA lesions, distinct macrophage phenotypes are associated with distinct functions and lesion morphology, dictated by local GM-CSF and M-CSF production.…”
Section: Introductionmentioning
confidence: 99%